EVALUASI RESIKO ERGONOMI PADA TRANSPORTASI AIR (SPEEDBOAT KAYU) Studi Kasus Kabupaten Indragiri Hilir Tembilahan - Khairul Ihwan (Program Studi Teknik Industri, 2018)
Water transportation is a means of transportation that is widely used by people in Indragiri Hilir regency in traveling from one place to another, the condition of areas separated by waters such as rivers, oceans and large canals requires the community to use water transportation such as canoes, speedboats and others. Speedboat is a water transportation that is widely used by masyarat because it has a higher speed than other transportation such as ships, canoes, and others. But there are some ergonomic risks that arise when using a speedboat, which makes passengers feel uncomfortable and safe, such as when going up / down from speedboat, shock due to sea waves, engine noise, the condition of the room is narrow and hot cause complaints of pain in body and several other complaints. This study examines the evaluation of ergonomic risks in wooden speedboats and provides recommendations based on ergonomics disciplines.